PHYSIOLOGICAL PARAMETERS OF STUDENTS DURING THE PROCESS OF ANSWERING THE COMPUTER TEACHING QUESTIONS - V. V. Andrianov; N. A. Vasilyuk; E. V. Biryukova; V. V. Kazakova (Сеченовский вестник, 2022)
Research of the psychological and physiological status of the medical students before and after solving the multiple choice questions were explored. Individual psychological and physiological parameters were studied in 2 groups of students (18–22 years old): 1 group — men and women; 2 – students who solved and not solved the tasks. It was shown that the dynamics of heart rhythm and parameters of haemodynamics illustrate vegetative maintenance of the intellectual activity of the students during solving computer teaching questions.